A case report on total pancreatic lipomatosis: An unusual entity - Kumar, Ravinder; Bhargava, Abhishek; Jaiswal, Gagan (International Journal of Health Sciences, 2017)
Total pancreatic lipomatosis (PL) is an unusual entity of pathologic significance and speculative origin. It refers to complete replacement of pancreatic parenchyma by fat cells. Fat replacement may vary from mild fatty infiltration to massive replacement of the pancreas by adipose tissue, resulting in malabsorption syndrome due to pancreatic insufficiency. We present a case of a 60-year-old elderly woman with atypical abdominal complaints, diabetes mellitus, weight loss, and steatorrhea. Abdominal computed tomograms were diagnostic of PL. Magnetic resonance imaging verified this impression. The patient improved clinically after the 8-week trial of high-dose oral pancreatic enzyme replacement therapy. There is a marked reduction of steatorrhea and weight gain. This case report focuses on pathophysiology, diagnosis, and treatment guidelines of PL.